2020
DOI: 10.3390/nu12082474
|View full text |Cite
|
Sign up to set email alerts
|

PHAGE-2 Study: Supplemental Bacteriophages Extend Bifidobacterium animalis subsp. lactis BL04 Benefits on Gut Health and Microbiota in Healthy Adults

Abstract: Probiotics are increasingly used by consumers and practitioners to reduce gastrointestinal (GI) distress and improve gut function. Here, we sought to determine whether the addition of supplemental bacteriophages (PreforPro) could enhance the effects of a common probiotic, Bifidobacterium animalis subsp. lactis (B. lactis) on GI health. A total of 68 participants were enrolled in a 4-week, randomized, parallel-arm, double-blind, placebo-controlled trial where primary outcomes included self-assessments of GI hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…Bacillus subtilis levels in samples was quantified by generation of standard curves using purified B. subtilis DNA (dilutions: 2–2 × 10 −5 ng DNA/rxn). Sequencing libraries were prepared following the Earth Microbiome Project protocols, as previously described [ 16 ]. Amplicon libraries were sequenced on an Illumina Miseq at the Next Generation Sequencing Core at Colorado State University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus subtilis levels in samples was quantified by generation of standard curves using purified B. subtilis DNA (dilutions: 2–2 × 10 −5 ng DNA/rxn). Sequencing libraries were prepared following the Earth Microbiome Project protocols, as previously described [ 16 ]. Amplicon libraries were sequenced on an Illumina Miseq at the Next Generation Sequencing Core at Colorado State University.…”
Section: Methodsmentioning
confidence: 99%
“… Symptom severity scores were based on answers to a GI symptom questionnaire by Metagenics [ 16 ] that is designed to provide a functional measure to assess symptoms associated with gastric function ( A ), gastrointestinal inflammation ( B ), small intestine/pancreas pain ( C ), and colon pain ( D ). Error bars represent ±SEM, # indicates a statistical trend ( p = 0.051–0.08).…”
Section: Figurementioning
confidence: 99%
“…In vivo targeting of specific bacterial pathogens with recombinant or wildtype phages was also investigated for Clostridium difficile infections [ 158 ], Vancomycin-resistant Enterococcus faecalis infections [ 159 ], Crohn’s disease [ 160 ] and even for the attenuation of alcoholic liver disease [ 161 ]. The human Bacteriophage for Gastrointestinal Health (PHAGE) study and PHAGE-2 study demonstrated that an application of therapeutic doses of bacteriophages was both safe and tolerable [ 162 , 163 , 164 ]. The double-blinded, placebo-controlled crossover PHAGE trial with adults consuming bacteriophages for 28 days (32/43 participants finished the study) also demonstrated that bacteriophages are able to selectively decrease the amount of target organisms, without disrupting the gut microbiome globally [ 162 ].…”
Section: Effect Of Dietary Compounds On Phagesmentioning
confidence: 99%
“…In the randomized, parallel-arm, double-blinded, placebo-controlled PHAGE-2 study (68 participants, four weeks), it could be shown that adding supplemental bacteriophages (PreforPro) to the probiotic Bifidobacterium animalis subsp. lactis enhanced positive effects on gastrointestinal health [ 164 ]. Taken together, there is increasing evidence, in initial in vivo studies, for the high potential of treating different diseases with bacteriophages and for the ability to reshape the gut microbiome via tailored phage cocktails.…”
Section: Effect Of Dietary Compounds On Phagesmentioning
confidence: 99%
“…The human body harbors a vast and complex microbiome that may contribute to both health and disease [37][38][39]. The impact of phage therapy on this flora is unclear.…”
Section: Impact Of Phage On the Microbiomementioning
confidence: 99%